Parker calls it quits after 46 years (Raton, New Mexico Raton Range, 1998)
Newspaper Article on Tom Parker's retirement from Safeway.
Master list item #: 16
File location is in the Raton File Cabinet
Keywords: Parker, Tom; Parker, Scott; Safeway; SuperSave; Local History; Biography; Life and Customs; Grocery Store; Employee; Retirement; Raton, New Mexico